Enhanced acupuncture therapy for radiotherapy-related neuropathic pain in patients with gynecologic cancer: a report of two cases and brief review - Dan-feng, Zhou; Jian-cheng, Rong; Shu-zhen, Zheng; Kun, Zhang; Hong-zhi, Yang; Lian-sheng, Yang; Chun-zhi, Tang (Frontiers in Neurology, 2023)
As radiation therapy is increasingly utilized in the treatment of cancer, neuropathic pain is common radiotherapy-related adverse event and has significant impact on clinical outcomes negatively. However, despite improved understanding of neuropathic pain management, pain is often under-treated in patients with cancer. Herein, we reported two cases with radiotherapy-related neuropathic pain(RRNP) who presented positive reaction to acupuncture. Patient 1 (a 73-year-old female) with gynecologic cancer complained of burning and electric shock-like pain in the lower limb after radiotherapy. Accepted combination of acupuncture and drugs, the pain was alleviated completely in 8 weeks. Patient 2 (a 64-year-old female) accepted acupuncture in the absence of medication because of inability to tolerate the adverse events of anticonvulsant drugs. She achieved remission of pain 4 weeks later. The results of this study showed that acupuncture might be promising for controlling the RRNP in patients with cancer, especially who were intolerant or unresponsive to medications.